EVALUATION OF THE RESULTS OF CALISTHENIC EXERCISE AND WALKING ON CHANGES IN BODY COMPOSITION IN ADOLESCENTS - Latola, Rozsyazwani Binti; Siantoro, Gigih; Sayaka, Rafi Fachri; Faiz, Mochammad Rifky Khoirul; Muchamad Riva`i; Rio Ferdian Saputra; Adinda Desi Lestari; Muhammad Cahyo Saputro Susanto; Matthew Mocodompis Mandak (Journal of Sport and Exercise Science, 2023)
This study aimed to explore the effect of physical activity on body composition and weight loss in healthy adolescents. Participants were divided into two groups: the Treatment group, who performed moderate physical activity at 75-85% intensity, and the control group, who performed physical activity at low intensity for 30 minutes of exercise per day. This study used descriptive tests to collect data and used statistical methods such as the Wilcoxon test to analyze the pre-test and post-test differences between the groups. The results showed a significant difference in body composition before and after the physical activity program. Body weight (BW), Body Mass Index (BMI), Body Fat Precentage (BFP), Fat Mass (FM), and Free Fat Mass (FFM) were significantly affected by the physical activity program. The increase in body weight was due to the adaptation of the muscular system and an effective hydrostatic hypertrophy mechanism. The study also found that the increase in muscle mass led to an increase in body weight and lean body mass index. This was due to the adaptation of the muscular system and the effect of the hydrostatic hypertrophy mechanism. This study concluded that physical activity can affect body metabolic rate (BMI) in adolescents, this study also found that regular physical activity can reduce the risk of obesity, such as type 2 diabetes and type 1 diabetes. These findings suggest that physical activity can be beneficial for maintaining a healthy body composition and weight